2020
DOI: 10.1093/mnras/staa2023
|View full text |Cite
|
Sign up to set email alerts
|

The inner gas mass–temperature profile in the core of nearby galaxy clusters

Abstract: We present a mass-temperature profile of gas within the central 10 kpc of a small sample of cool core clusters. The mass of the hottest gas phases, at 1.5 and 0.7 keV, is determined from X-ray spectra from the XMM Reflection Grating Spectrometers. The masses of the partially ionised atomic and the molecular phases are obtained from published Hα and CO measurements. We find that the mass of gas at 0.7 keV in a cluster is remarkably similar to that of the molecular gas. Assuming pressure equilibrium between the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…Although our cooling flow models find most gas is above 0.7 keV, the detection of the Fe XVII resonance line shows that it is likely to have some cool gas at around 0.5 keV. Liu et al (2020) measured the mass of 0.7 keV in nearby cool core clusters of 10 8 − 10 9 M . RXCJ1504 is likely to have a higher gas mass at this temperature, since the luminosity of the 0.7 keV gas in the two-temperature model is 9 times larger than that of 2A0335+096, which has the largest gas mass below 1 keV.…”
Section: 𝑘𝑇 1kevmentioning
confidence: 59%
See 2 more Smart Citations
“…Although our cooling flow models find most gas is above 0.7 keV, the detection of the Fe XVII resonance line shows that it is likely to have some cool gas at around 0.5 keV. Liu et al (2020) measured the mass of 0.7 keV in nearby cool core clusters of 10 8 − 10 9 M . RXCJ1504 is likely to have a higher gas mass at this temperature, since the luminosity of the 0.7 keV gas in the two-temperature model is 9 times larger than that of 2A0335+096, which has the largest gas mass below 1 keV.…”
Section: 𝑘𝑇 1kevmentioning
confidence: 59%
“…The condensation of X-ray cooling gas is strongly linked to both the massive molecular gas reservoir and the star formation in the BCG, which are only present when the radiative cooling time falls below a Gyr (Rafferty et al 2008;Pulido et al 2018). Russell et al (2019) and Liu et al (2020) found that the mass of the soft X-ray gas is consistent with the molecular gas mass in the inner 10 kpc. If the X-ray cooling flow is indeed a major source of gas for the molecular gas reservoir and then star formation, we can calculate the timescale for forming the reservoir.…”
Section: 𝑘𝑇 1kevmentioning
confidence: 99%
See 1 more Smart Citation